Corrosion Rate Analysis of An Excavator Bucket (A Case Study at the Heavy Equipment Workshop Unit of the Public Works and Spatial Planning Agency (PUPR) of Bengkalis Regency) - Edi Hartono; Ibnu Hajar (International Journal of Science and Environment (IJSE), 2026)
Corrosion is a common issue affecting heavy equipment components, particularly excavator buckets that operate in open environments and frequently come into direct contact with water, mud, soil, and abrasive materials. Continuous corrosion can lead to reduced material thickness, mass loss, and diminished mechanical strength, ultimately shortening the excavator bucket's service life. This study aims to determine the corrosion rate of excavator buckets at the Heavy Equipment Workshop Unit (UPT) of the Bengkalis Regency Public Works and Spatial Planning Agency (Dinas PUPR). The study employed a quantitative method using the weight-loss approach. Data were obtained through direct measurement of excavator bucket dimensions, measurement of initial and actual thicknesses, and calculations of volume, material density, mass loss, and exposure time during the service period. The collected data were then analyzed using the corrosion rate formula to quantify the extent of corrosion on the excavator buckets. The results indicate that the excavator bucket has a surface area of ​​14,712 cm², a volume of 99,360 cm³, and a material density of 8.05 g/cm³. The reduction in bucket thickness from 50 mm to 41 mm represents a loss of 9 mm (or 0.9 cm). Calculations revealed a material volume loss of 13,240.8 cm³ and a mass loss of 106,588.44 grams. The total exposure time for the excavator bucket during its service period was 6,300 hours. Analysis using the weight-loss method yielded a corrosion rate of 12.50 mm/year. In conclusion, the excavator buckets at the Bengkalis Regency PUPR Agency's Heavy Equipment Workshop are experiencing a relatively high rate of corrosion. This condition is driven by the bucket's operating environment, which involves frequent exposure to water, mud, and high humidity, as well as material friction during operations. Therefore, routine maintenance, periodic thickness inspections, and the application of anti-corrosion coatings are necessary to slow the corrosion rate and extend the service life of the excavator buckets.